THE BOC'S EFFECTIVENESS TO ENHANCE THE ESP INDUSTRIAL ENGINEERING - Suhardiman, Sani; Suhara, Ade; Rahdiana, Nana; Pratama, Yuda; Suryani Afifah, Early (Information Technology Education Department, 2024)
ESP is seen as the role of English in language teaching courses, where the content and learning objectives are determined by the specific needs of a particular group of learners. Likewise, English for Specific Purposes is a stimulus for students' needs and language acquisition relevant to the work they will face in the future. This study aims to find out the use and effectiveness of BOC in conducting the material of engineering class and values of the teaching program and the needs of students. The quantitative study questionnaire is spread out to 200 students. The result shows that 30% of students think that the Buana Online Course (BOC) plays a good role in engineering studies and 25% of students think that it is very important for learning in engineering classes. Furthermore, 30.70% of students agreed that BOC is effective and 26. 50% of students strongly agreed that applying BOC is effective in engineering research practice. These results indicate that a significant proportion of students found BOC beneficial to their engineering studies.